High-strength heat-resistant wrought magnesium alloy and preparation method thereof

By using the combination of Gd, La, Zn, Zr and other elements in magnesium alloys, the synergistic effect of light and heavy rare earth elements and the formation of intermetallic compounds, the problem of insufficient strength and heat resistance of traditional magnesium alloys is solved, and high strength is achieved It has low cost high temperature mechanical properties, suitable for manufacturing structural parts around 200℃.

CN119194192APending Publication Date: 2024-12-27CHANGCHUN INST OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411305837.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-19
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Due to its low strength and poor heat resistance, traditional magnesium alloys have limited their large-scale engineering applications. The high rare earth content leads to an increase in alloy density and cost, which violates the original intention of lightweight and cost control. How to maintain or improve performance while maintaining or improving performance. Reducing rare earth content becomes a challenge.

Method used

Using a high-strength heat-resistant deformation magnesium alloy with a component ratio of Gd 8.0 to 9.0%, La 0 to 1.0%, Zn 1.0 to 1.5%, Zr 0.4 to 0.6%, by removing raw material oxide layer, alloy smelting, hydrogen removal and refining, and extrusion. Preparation is carried out by press processing and other steps, using the synergistic effect of light and heavy rare earth elements to improve the aging and strengthening effect of the alloy, and hindering the movement of dislocations through intermetallic compounds to improve mechanical properties.

Benefits of technology

It achieves the improvement of the tensile strength, yield strength and heat resistance of the alloy while reducing the rare earth content, significantly reduces the preparation cost, and maintains excellent mechanical properties under high temperature conditions. It is suitable for the manufacture of high-temperature structural parts.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194192A_ABST
    Figure CN119194192A_ABST
Patent Text Reader

Abstract

The invention is suitable for the technical field of nonferrous metal materials and processing thereof, and provides a high-strength heat-resistant wrought magnesium alloy and a preparation method thereof. Two light and heavy rare earth elements, namely gadolinium and lanthanum, are compounded and added, so that the solid solubility of the two rare earth elements in a magnesium matrix is reduced, the effects of grain refinement and second phase strengthening are enhanced, and the use amount of the rare earth is reduced so as to reduce the cost. An intermetallic compound with a high melting point and good thermal stability is formed in the casting process, and the mechanical property and the heat resistance of the alloy can be remarkably improved. The high-strength heat-resistant wrought magnesium alloy subjected to component optimization shows excellent mechanical properties: at 25 DEG C, the tensile strength is 406 MPa, the yield strength is 398 MPa, and the ductility is 5.5%; at the temperature of 200 DEG C, the tensile strength is 372 MPa, the yield strength is 342 MPa, and the ductility is 7.1%; and at the temperature of 250 DEG C, the tensile strength is 325 MPa, the yield strength is 301 MPa, and the ductility is 17.6%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of nonferrous metal materials and processing thereof, and in particular relates to a high-strength heat-resistant deformable magnesium alloy and a preparation method thereof. Background Art

[0002] With the booming development of the global automobile industry and the intensification of energy and environmental challenges, automobile lightweighting has become one of the key ways to alleviate energy consumption and emission pressures, which has greatly promoted the application of magnesium alloys in the automobile industry. However, the low strength and poor heat resistance of traditional magnesium alloys limit their large-scale engineering applications. Rare earth (RE) elements can effectively improve the room temperature and high temperature strength of magnesium alloys. The currently developed Mg-Gd(-Y-Zn)-Zr alloy has good strength and heat resistance. It has become a research hotspot in the field of high-performance magnesium alloys by virtue of its strong aging hardening effect and excellent mechanical properties. Among these alloys, the high-strength Mg-10Gd-5.7Y-1.6Zn-0.7Zr (wt%) alloy has a tensile strength of 542MPa and a yield strength of 473MPa. The high-strength Mg-11.7Gd-4.5Y-1Nd-1.5Zn-0.5Zr (wt%) deformed alloy has a tensile strength of 547MPa and a yield strength of 502MPa. However, the high rare earth content in the alloy system (≥12wt%) will significantly increase the alloy density and cost, which goes against the original intention of lightweighting and cost control of magnesium alloys. Therefore, how to effectively reduce the rare earth content while maintaining or improving performance has become a bottleneck that needs to be broken through in the research and development of high-strength and heat-resistant rare earth magnesium alloys.

[0003] Studies have shown that when two different rare earth elements are added to a magnesium alloy at the same time, the two elements reduce each other's solid solubility in the magnesium matrix and optimize each other's aging precipitation behavior. This synergistic effect greatly enhances the aging strengthening effect of the alloy. For example, after rolling and aging treatment, the tensile strength of the Mg-8Gd-1Er-0.5Zr (wt%) alloy reaches 560MPa and the yield strength reaches 518MPa. Its mechanical properties are higher than those of other traditional magnesium alloys with high rare earth content, but its ultra-large deformation rolling process is difficult to commercialize.

[0004] my country's light rare earth reserves are much higher than heavy rare earths, but most of the light rare earths have not been effectively utilized. The development of light and heavy rare earth composite strengthening alloys can improve the utilization rate of light rare earths and significantly reduce the dependence on more expensive heavy rare earths, which is of great significance for promoting the effective and rational utilization of my country's rare earth resources. Based on the above, the present invention proposes a high-strength heat-resistant deformable magnesium alloy and a preparation method thereof. Summary of the invention

[0005] The object of the present invention is to provide a high-strength heat-resistant deformable magnesium alloy and a preparation method thereof, aiming to solve the problems raised in the above-mentioned background technology.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A high-strength heat-resistant deformable magnesium alloy comprises the following components in percentage by mass: 8.0-9.0% Gd, 0-1.0% La, 1.0-1.5% Zn, 0.4-0.6% Zr, inevitable impurities ≤0.011%, and the balance Mg.

[0008] Furthermore, the unavoidable impurities include Fe, Cu, Si and Ni, and the mass percentages of the impurity elements are respectively: Fe≤0.005%, Cu≤0.0005%, Si≤0.005%, Ni≤0.0005%.

[0009] Further, the following components are included in mass percentage: Gd 8.0%, La 0.75%, Zn 1.2%, Zr 0.5%, and the balance is Mg and inevitable impurities.

[0010] A method for preparing the above-mentioned high-strength heat-resistant deformable magnesium alloy comprises the following steps:

[0011] Step 1, raw material preparation: remove the oxide layer on the surface of magnesium ingot (Mg), zinc ingot (Zn), gadolinium source (Gd), lanthanum source (La) and zirconium source (Zr), weigh the raw materials according to the ratio and preheat the raw materials to 200-300° C.;

[0012] Step 2, alloy smelting: heating the crucible, when the temperature reaches 550°C, adding the magnesium ingot and introducing the protective gas to prevent oxidation; after the magnesium ingot is melted, continue to heat up to 730-740°C, and add the zinc ingot, gadolinium source and lanthanum source in sequence, after the added raw materials are melted, remove the scum on the surface of the melt, and stir for 10-20 minutes; further heat up to 760-780°C, add the zirconium source, after the zirconium source is melted, add No. 6 flux and keep warm for 10 minutes;

[0013] Step 3, dehydrogenation refining: lower the temperature to 750°C and introduce argon for 30 seconds; after the ventilation is completed, add the refining agent while stirring until the refining agent is completely integrated into the melt, and then let it stand for 50 to 60 minutes;

[0014] Step 4, casting out of the furnace: after standing, cool down to 720-740°C, remove scum on the surface of the melt again, and then pour the melt into a water-cooled steel mold to obtain alloy casting rods;

[0015] Step 5, extrusion processing: removing the oxide layer on the surface of the alloy casting rod by turning, and performing extrusion processing, the extrusion parameters are: extrusion temperature is 340°C, holding time is 70-100min, extrusion ratio is 17.64, extrusion speed is 0.1-0.2mm / s; the extrusion die is kept at the extrusion temperature for at least 40min before extrusion; finally, a high-strength heat-resistant deformable magnesium alloy is obtained.

[0016] Furthermore, in step 1, the gadolinium source is a magnesium-gadolinium master alloy containing 20% ​​gadolinium, the lanthanum source is a magnesium-lanthanum master alloy containing 20% ​​lanthanum, and the zirconium source is a magnesium-zirconium master alloy containing 30% zirconium.

[0017] Furthermore, in step 2, the protective gas is a gas mixed with SF6 and CO2 in a volume ratio of 1:200.

[0018] Furthermore, in step 2, No. 6 flux is a product well known to those skilled in the art and can be obtained commercially. The amount of No. 6 flux added is 1.0-1.5% of the total mass of each raw material; No. 6 flux includes the following components in mass percentage: KCl 54-56%, BaCl2 14-16%, NaCl 1.5-2.5%, CaCl2 27-29%.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The present invention proposes a high-strength, heat-resistant and deformable magnesium alloy with light rare earth lanthanum and heavy rare earth gadolinium as main alloying elements. On the one hand, rare earths can increase the degree of supercooling and help refine the grains, thereby effectively improving the plasticity of the cast alloy and facilitating subsequent extrusion deformation; on the other hand, adding rare earth elements from different groups to the magnesium matrix at the same time can reduce each other's solid solubility in the magnesium matrix, better exert the second phase strengthening effect, and reduce the rare earth content at the same time, thereby reducing the preparation cost.

[0021] 2. The present invention forms intermetallic compounds with relatively high melting points and good thermal stability during the casting process, such as Mg3(Gd, La) and Mg 12 (Gd, La), these second phases with good thermal stability can effectively hinder dislocation movement and grain boundary sliding under high temperature conditions, thereby significantly improving the mechanical properties and heat resistance of the alloy.

[0022] 3. The high-strength heat-resistant deformable magnesium alloy after component optimization in the present invention exhibits excellent mechanical properties: at 25°C, the tensile strength is 406MPa, the yield strength is 398MPa, and the elongation is 5.5%; at 200°C, the tensile strength is 372MPa, the yield strength is 342MPa, and the elongation is 7.1%; at 250°C, the tensile strength is 325MPa, the yield strength is 301MPa, and the elongation is 17.6%. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is the original cast structure of the deformed magnesium alloy prepared in Example 3.

[0024] Figure 2 This is the deformed structure of the deformed magnesium alloy prepared in Example 3 obtained after extrusion at 340°C. DETAILED DESCRIPTION

[0025] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0026] The specific implementation of the present invention is described in detail below in conjunction with specific embodiments.

[0027] Embodiment 1: A high-strength heat-resistant deformable magnesium alloy, wherein the mass percentages of the components are: Gd 8.0%, La 0.25%, Zn 1.2%, Zr 0.4%, and the balance is Mg and unavoidable impurities.

[0028] The preparation steps are as follows:

[0029] (1) Raw material preparation: remove the oxide layer on the surface of magnesium ingot, zinc ingot, gadolinium source, lanthanum source and zirconium source, weigh the raw materials according to the ratio and preheat the raw materials to 200°C.

[0030] (2) Alloy smelting: Heat the crucible. When the temperature reaches 550°C, add the magnesium ingot and introduce protective gas to prevent oxidation. After the magnesium ingot melts, continue to heat it to 730°C and add the zinc ingot, gadolinium source and lanthanum source in turn. After they melt, skim off the scum on the surface of the melt and stir for 10 minutes. Then heat it to 760°C and add the zirconium source. After the zirconium source melts, add No. 6 flux, the amount added is 1.0% of the total mass of each raw material, and keep it warm for 10 minutes.

[0031] (3) Refining by removing hydrogen: Lower the temperature to 750°C, introduce high-purity argon gas, and use an appropriate gas flow rate to prevent liquid splashing for 30 seconds. After the gas flow is completed, add the refining agent while stirring, and let it stand for 50 minutes after the refining agent is fully integrated into the melt.

[0032] (4) Casting: After standing, cool to 720℃, skim off the scum on the surface of the melt, and then pour the melt into a water-cooled steel mold at an appropriate casting speed to obtain alloy cast bars.

[0033] (5) Extrusion processing: The oxide layer on the surface of the alloy casting rod is removed by turning, and then extrusion processing is performed. The extrusion parameters are: extrusion temperature is 340°C, holding time is 75 minutes, extrusion ratio is 17.64, and extrusion speed is 0.1 mm / s; the extrusion die is kept at the extrusion temperature for 45 minutes before extrusion. Finally, a high-strength heat-resistant deformable magnesium alloy rod is obtained.

[0034] The mechanical properties of the high-strength heat-resistant deformable magnesium alloy of Example 1 were tested, and the results are shown in Table 1.

[0035] Table 1 Room temperature and high temperature mechanical properties of the deformed magnesium alloy in Example 1

[0036]

[0037] Embodiment 2: A high-strength heat-resistant deformable magnesium alloy, wherein the mass percentages of the components are: Gd 8.0%, La 0.5%, Zn 1.2%, Zr 0.5%, and the balance is Mg and unavoidable impurities.

[0038] The preparation steps are as follows:

[0039] (1) Raw material preparation: remove the oxide layer on the surface of magnesium ingot, zinc ingot, gadolinium source, lanthanum source and zirconium source, weigh the raw materials according to the ratio and preheat the raw materials to 250°C.

[0040] (2) Alloy smelting: Heat the crucible. When the temperature reaches 550°C, add the magnesium ingot and introduce protective gas to prevent oxidation. After the magnesium ingot is melted, continue to heat it to 740°C, and add the zinc ingot, gadolinium source and lanthanum source in turn. After they are melted, skim off the scum on the surface of the melt and stir for 10 minutes. Then heat it to 780°C, add the zirconium source, and after the zirconium source is melted, add No. 6 flux, the amount added is 1.0% of the total mass of each raw material, and keep it warm for 10 minutes.

[0041] (3) Refining by removing hydrogen: Lower the temperature to 750°C, introduce high-purity argon gas, and use an appropriate gas flow rate to prevent liquid splashing for 30 seconds. After the gas flow is completed, add the refining agent while stirring, and let it stand for 60 minutes after the refining agent is fully integrated into the melt.

[0042] (4) Casting: After standing, cool to 730℃, skim off the scum on the surface of the melt, and then pour the melt into a water-cooled steel mold at an appropriate casting speed to obtain alloy cast bars.

[0043] (5) Extrusion processing: The oxide layer on the surface of the alloy casting rod is removed by turning, and then extrusion processing is performed. The extrusion parameters are: extrusion temperature is 340°C, holding time is 80 minutes, extrusion ratio is 17.64, and extrusion speed is 0.1 mm / s; the extrusion die is kept at the extrusion temperature for 45 minutes before extrusion. Finally, a high-strength heat-resistant deformable magnesium alloy rod is obtained.

[0044] The mechanical properties of the high-strength heat-resistant deformable magnesium alloy of Example 2 were tested, and the results are shown in Table 2.

[0045] Table 2 Room temperature and high temperature mechanical properties of the deformed magnesium alloy in Example 2

[0046]

[0047] Embodiment 3: A high-strength heat-resistant deformable magnesium alloy, wherein the mass percentages of the components are: Gd 8.0%, La 0.75%, Zn 1.2%, Zr 0.5%, and the balance is Mg and unavoidable impurities.

[0048] The preparation steps are as follows:

[0049] (1) Raw material preparation: remove the oxide layer on the surface of the magnesium ingot, zinc ingot, gadolinium source, lanthanum source and zirconium source, weigh the raw materials according to the ratio and preheat the raw materials to 300°C.

[0050] (2) Alloy smelting: Heat the crucible. When the temperature reaches 550°C, add the magnesium ingot and introduce protective gas to prevent oxidation. After the magnesium ingot is melted, continue to heat it to 740°C, and add the zinc ingot, gadolinium source and lanthanum source in turn. After they are melted, skim off the scum on the surface of the melt and stir for 10 minutes. Then heat it to 780°C, add the zirconium source, and after the zirconium source is melted, add No. 6 flux, the amount added is 1.0% of the total mass of each raw material, and keep it warm for 10 minutes.

[0051] (3) Refining by removing hydrogen: Lower the temperature to 750°C, introduce high-purity argon gas, and use an appropriate gas flow rate to prevent liquid splashing for 30 seconds. After the gas flow is completed, add the refining agent while stirring, and let it stand for 60 minutes after the refining agent is fully integrated into the melt.

[0052] (4) Casting: After standing, cool to 740℃, skim off the scum on the surface of the melt, and then pour the melt into a water-cooled steel mold at an appropriate casting speed to obtain alloy cast bars.

[0053] (5) Extrusion processing: The oxide layer on the surface of the alloy casting rod is removed by turning, and then extrusion processing is performed. The extrusion parameters are: extrusion temperature is 340°C, holding time is 90 minutes, extrusion ratio is 17.64, and extrusion speed is 0.1 mm / s; the extrusion die is kept at the extrusion temperature for 45 minutes before extrusion. Finally, a high-strength heat-resistant deformable magnesium alloy rod is obtained.

[0054] The mechanical properties of the high-strength heat-resistant deformable magnesium alloy of Example 3 were tested, and the results are shown in Table 3.

[0055] Table 3 Room temperature and high temperature mechanical properties of the deformed magnesium alloy in Example 3

[0056]

[0057]

[0058] Embodiment 4: A high-strength, heat-resistant, deformable magnesium alloy, wherein the mass percentages of the components are: Gd 8.0%, La 1.0%, Zn 1.2%, Zr 0.5%, and the balance is Mg and unavoidable impurities.

[0059] The preparation steps are as follows:

[0060] (1) Raw material preparation: remove the oxide layer on the surface of the magnesium ingot, zinc ingot, gadolinium source, lanthanum source and zirconium source, weigh the raw materials according to the ratio and preheat the raw materials to 300°C.

[0061] (2) Alloy smelting: Heat the crucible. When the temperature reaches 550°C, add the magnesium ingot and introduce protective gas to prevent oxidation. After the magnesium ingot melts, continue to heat it to 730°C and add the zinc ingot, gadolinium source and lanthanum source in turn. After they melt, skim off the scum on the surface of the melt and stir for 10 minutes. Then heat it to 780°C and add the zirconium source. After the zirconium source melts, add No. 6 flux, the amount added is 1.0% of the total mass of each raw material, and keep it warm for 10 minutes.

[0062] (3) Refining by removing hydrogen: Lower the temperature to 750°C, introduce high-purity argon gas, and use an appropriate gas flow rate to prevent liquid splashing for 30 seconds. After the gas flow is completed, add the refining agent while stirring, and let it stand for 60 minutes after the refining agent is fully integrated into the melt.

[0063] (4) Casting: After standing, cool to 720℃, skim off the scum on the surface of the melt, and then pour the melt into a water-cooled steel mold at an appropriate casting speed to obtain alloy cast bars.

[0064] (5) Extrusion processing: The oxide layer on the surface of the alloy casting rod is removed by turning, and then extrusion processing is performed. The extrusion parameters are: extrusion temperature is 340°C, holding time is 75 minutes, extrusion ratio is 17.64, and extrusion speed is 0.1 mm / s; the extrusion die is kept at the extrusion temperature for 45 minutes before extrusion. Finally, a high-strength heat-resistant deformable magnesium alloy rod is obtained.

[0065] The mechanical properties of the high-strength heat-resistant deformable magnesium alloy of Example 4 were tested, and the results are shown in Table 4.

[0066] Table 4 Room temperature and high temperature mechanical properties of the deformed magnesium alloy in Example 4

[0067]

[0068]

[0069] As shown in Tables 1 to 4, the deformed magnesium alloy prepared in Example 3 has high strength and plasticity at room temperature, and the yield strength is greater than 340 MPa at 200°C. Therefore, the deformed alloy is expected to be used for manufacturing structural parts with a service temperature of about 200°C. At 250°C, the alloy remains in a softened state after yielding, showing high elongation. Figure 1 This is the original cast structure of the deformed magnesium alloy prepared in Example 3. It can be seen from the figure that the structure is relatively uniform and the average grain size is about 36 microns. Figure 2 The deformed structure of the deformed magnesium alloy prepared in Example 3 obtained after extrusion at 340°C is significantly finer than the original casting structure after extrusion deformation, and the recrystallized area and the non-recrystallized area can be clearly seen. The average grain size of the recrystallized grains is about 1.38 microns.

[0070] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.

Claims

1. A high-strength heat-resistant deformable magnesium alloy, characterized in that: The invention comprises the following components in mass percentage: Gd 8.0-9.0%, La 0-1.0%, Zn 1.0-1.5%, Zr 0.4-0.6%, unavoidable impurities ≤0.011%, and the balance is Mg.

2. The high-strength heat-resistant deformable magnesium alloy according to claim 1, characterized in that: The unavoidable impurities include Fe, Cu, Si and Ni, and the mass percentages of the impurity elements are respectively: Fe≤0.005%, Cu≤0.0005%, Si≤0.005%, Ni≤0.0005%.

3. The high-strength heat-resistant deformable magnesium alloy according to claim 1, characterized in that: The composition includes the following components in mass percentage: Gd 8.0%, La 0.75%, Zn 1.2%, Zr 0.5%, and the balance is Mg and inevitable impurities.

4. A method for preparing a high-strength heat-resistant deformable magnesium alloy according to any one of claims 1 to 3, characterized in that: The following steps are involved: Step 1, raw material preparation: remove the oxide layer on the surface of magnesium ingot, zinc ingot, gadolinium source, lanthanum source and zirconium source, weigh the raw materials according to the ratio and preheat the raw materials to 200-300° C.; Step 2, alloy smelting: heating the crucible, when the temperature reaches 550°C, adding the magnesium ingot and introducing the protective gas, after the magnesium ingot is melted, continue to heat up to 730-740°C, and add the zinc ingot, gadolinium source and lanthanum source in sequence, after the added raw materials are melted, remove the scum on the surface of the melt, and stir for 10-20 minutes; further heat up to 760-780°C, add the zirconium source, after the zirconium source is melted, add No. 6 flux and keep warm for 10 minutes; Step 3, dehydrogenation refining: lower the temperature to 750°C and introduce argon for 30 seconds; after the ventilation is completed, add the refining agent while stirring until the refining agent is completely integrated into the melt, and then let it stand for 50 to 60 minutes; Step 4, casting out of the furnace: after standing, cool down to 720-740°C, remove scum on the surface of the melt again, and then pour the melt into a water-cooled steel mold to obtain alloy casting rods; Step 5, extrusion processing: removing the oxide layer on the surface of the alloy casting rod by turning, and performing extrusion processing, the extrusion parameters are: extrusion temperature is 340°C, holding time is 70-100min, extrusion ratio is 17.64, extrusion speed is 0.1-0.2mm / s; the extrusion die is kept at the extrusion temperature for at least 40min before extrusion; finally, a high-strength heat-resistant deformable magnesium alloy is obtained.

5. The preparation method according to claim 4, characterized in that: In the step 1, the gadolinium source is a magnesium-gadolinium master alloy containing 20% ​​gadolinium, the lanthanum source is a magnesium-lanthanum master alloy containing 20% ​​lanthanum, and the zirconium source is a magnesium-zirconium master alloy containing 30% zirconium.

6. The preparation method according to claim 4, characterized in that: In step 2, the protective gas is a gas mixed with SF6 and CO2 in a volume ratio of 1:

200.

7. The preparation method according to claim 4, characterized in that: In the step 2, the amount of No. 6 flux added is 1.0-1.5% of the total mass of the raw materials; the No. 6 flux includes the following components in mass percentage: KCl 54-56%, BaCl2 14-16%, NaCl 1.5-2.5%, and CaCl2 27-29%.